Strengthening Anti-Corruption Education Values among Millennials through Community-Based Civic Education: A Community Service Program in Lubuklinggau, Indonesia - Heru Prasetyo (Edupro: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2026)
This community service program aimed to strengthen anti-corruption education values among millennials. The program was designed as a qualitative-descriptive community engagement activity through educational outreach, lecture, guided discussion, value clarification, and reflective questioning. The activity was held at IAI Al-Azhaar Lubuklinggau, South Sumatra, and involved students, community members, and anti-corruption activists. The results show that the program strengthened participants’ conceptual awareness of corruption as a legal, moral, and social problem; introduced the nine anti-corruption values as practical guides for everyday behavior; and encouraged dialogic reflection on the causes, risks, and prevention of corrupt practices. The program also provided space for participants to connect anti-corruption values with student life, social organizations, digital spaces, and future professional roles. Although the activity was limited by its one-time implementation, the absence of pre-test and post-test instruments, and incomplete attendance documentation, it offers an initial model of value-based anti-corruption literacy. The implication is that anti-corruption community service programs should be developed continuously, measurably, participatorily, and collaboratively to strengthen youth integrity and civic responsibility.